Winery wastewater characterisation, monitoring and treatment evaluation using an air micro-bubble bioreactor - Oliveira, Maria Margarida da Costa Ferreira Correia de (2013)
Doutoramento em Engenharia do Ambiente - Instituto Superior de Agronomia